TRANSLATION SHIFT USED IN ECONOMIC BILINGUAL TEXT BOOK - RATNA SORAYA (JURNAL ILMIAH KOHESI, 2019)
The aims of this research were to find out the kinds of translation shift in translation of Economic Bilingual Text Book, to describe the pattern of shift used by Economic Bilingual Text Book to bridge the different grammatical structures between Indonesia and English, and to explain about the reason of translation shift used in Economic Bilingual Text Book. The research was conducted by using qualitative descriptive design. The data of this study was clauses that were translated from Bahasa Indonesia into English by Mulyadi, E., and Mardiyatmo (2009) on an Economic Bilingual text book ‘Economics 1’ for Junior High School Year VII as the source of data. The data was analyzed by using the Theory of Translation Shift based on (Catford: 1965) to find the types and the ways of translation shift used in economic bilingual text book and the reasons of translation shift were used in Economic Bilingual Text Book based on Newmark (1988:85).